Barriers of the CNS transfer rate dynamics in patients with vascular cognitive impairment and dementia - Taheri, Saeid; Prestopnik, Jill; Rosenberg, Gary A. (Frontiers in Aging Neuroscience, 2024)
Background Advances in in vivo MRI techniques enable cerebral barrier transfer rates (Ktrans) measurement in patients with vascular cognitive impairment and dementia (VCID). However, a consensus has not been reached on the dynamic contribution and importance of cerebral barrier abnormalities to the differential diagnosis of dementia subtypes. Our goal was to investigate the dynamics of blood-brain barrier (BBB) and blood-CSF barrier (BCSFB) Ktrans in patients with VCID longitudinally and determine the effect of aging. Methods We studied subjects at two time points over two years; they were 65.5 years of age (SD = 15.94, M/F = 24/14) at the first visit. We studied 38 patients, 18 of whom had two visits. We calculated the BBB and BCSFB Ktrans with dynamic contrast-enhanced T1 MR, and we used 1H-MR spectroscopy to measure N-acetylaspartate (NAA) levels in the white matter as a marker of injury. In addition, we measured CSF levels of active-matrix metalloproteinase-3 (MMP3) as an inflammatory biomarker to aid in patient clustering. Results Longitudinal BBB measurements revealed variable dynamic behavior: after two years, the BBB Ktrans increased in 55% of patients and decreased in the remaining 45% unpredictably. We did not find a significant linear model of BBB Ktrans versus age for VCID. For healthy controls, the model was Ktrans = 0.0014 + 0.0002 × age, which was significant (p = 0.046). VCID patients showed a reduction in BCSFB Ktrans compared to healthy controls (p = 0.01). Combining NAA, CSF MMP3, and Ktrans in a clustering analysis separated patients into groups. Conclusion These results suggest that BBB Ktrans in VCID is dynamic and BCSFB Ktrans reduced by age. By combining inflammatory biomarkers with BBB Ktrans data, it is possible to separate VCID patients into distinct groups with different underlying pathologies.